Endothelial Microparticles in Uremia: Biomarkers and Potential Therapeutic Targets - Giane Favretto; Regiane Stafim da Cunha; Maria Aparecida Dalboni; Rodrigo Bueno de Oliveira; Fellype de Carvalho Barreto; Ziad A. Massy; Andréa Emilia Marques Stinghen (Toxins, 2019)
Endothelial microparticles (EMPs) are vesicles derived from cell membranes, which contain outsourced phosphatidylserine and express adhesion molecules, such as cadherin, intercellular cell adhesion molecule-1 (ICAM-1), E-selectin, and integrins. EMPs are expressed under physiological conditions and continue circulating in the plasma. However, in pathologic conditions their levels increase, and they assume a pro-inflammatory and pro-coagulant role via interactions with monocytes; these effects are related to the development of atherosclerosis. Chronic kidney dysfunction (CKD) characterizes this dysfunctional scenario through the accumulation of uremic solutes in the circulating plasma, whose toxicity is related to the development of cardiovascular diseases. Therefore, this review aims to discuss the formation of EMPs and their biological effects in the uremic environment. Data from previous research demonstrate that uremic toxins are closely associated with the activation of inflammatory biomarkers, cardiovascular dysfunction processes, and the release of EMPs. The impact of a decrease in circulating EMPs in clinical studies has not yet been evaluated. Thus, whether MPs are biochemical markers and/or therapeutic targets has yet to be established.